2018
DOI: 10.1186/s12881-018-0692-8
|View full text |Cite
|
Sign up to set email alerts
|

Novel mutations in TPM2 and PIEZO2 are responsible for distal arthrogryposis (DA) 2B and mild DA in two Chinese families

Abstract: BackgroundDistal arthrogryposis (DA) is a group of clinically and genetically heterogeneous disorders that involve multiple congenital limb contractures and comprise at least 10 clinical subtypes. Here, we describe our findings in two Chinese families: Family 1 with DA2B (MIM 601680) and Family 2 with mild DA.MethodsTo map the disease locus, two-point linkage analysis was performed with microsatellite markers closed to TPM2, TNNI2/TNNT3 and TNNC2. In Family 1, a positive LOD (logarithm of odds) score was only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Individuals diagnosed with Dehydrated Hereditary Stomatocytosis (DHSt) were found to have a missense mutation in a conserved arginine residue (R2488Q) of PIEZO1. The orthologous residue (R2718L/P) was also mutated in PIEZO2 in individuals with Distal Arthrogryposis type 5 (DA5) ( Andolfo et al, 2013 ; Coste et al, 2013 ; Li et al, 2018 ; McMillin et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Individuals diagnosed with Dehydrated Hereditary Stomatocytosis (DHSt) were found to have a missense mutation in a conserved arginine residue (R2488Q) of PIEZO1. The orthologous residue (R2718L/P) was also mutated in PIEZO2 in individuals with Distal Arthrogryposis type 5 (DA5) ( Andolfo et al, 2013 ; Coste et al, 2013 ; Li et al, 2018 ; McMillin et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that these arginine changes are functioning as gain-of-function mutations in their respective PIEZO protein ( Albuisson et al, 2013 ; Coste et al, 2013 ; Li et al, 2018 ; McMillin et al, 2014 ). Sequence alignment indicated that R2405 in C. elegans PEZO-1 is the arginine residue homologous to both R2488 in human PEIZO1 and R2718 in human PIEZO2 ( Figure 9A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intellectual disability is a typical symptom of Marden-Walker syndrome caused by PIEZO2 gain-of-function variants (McMillin et al, 2014 ). This syndrome typically involves congenital contractures of hands and feet, or cleft palate, ophthalmoplegia, ptosis, and cerebellar malformations (Li et al, 2018 ). We could not exclude the partial clinical overlap with this syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…TPM2 variants are causative of DA type 1 (DA1) (Sung et al, 2003), which is characterized by contractures of the hands and feet including permanently bent fingers (camptodactyly) and clubfoot (talipes equinovarus) (Bamshad et al, 2009). TPM2 variants are also associated with DA type 2B (DA2B) (Li et al, 2018;Tajsharghi et al, 2007a), which is characterized by facial abnormalities in addition to contractures of the extremities (Bamshad et al, 2009). DA patients often show hypotonia (Marttila et al, 2014;Mroczek et al, 2017), arguing skeletal muscle dysfunction contributes to the overall disease mechanism.…”
Section: Introductionmentioning
confidence: 99%